Panorama da gestão ambiental no município de Lavras, em Minas Gerais - Vieira, Érico Gonçalves Alves (2021)
Despite being one of the most biodiverse biomes worldwide, the Atlantic Forest is threatened by constant deforestation and is considered a global hotspot. In 2019, Minas Gerais was the state that most deforested areas of Atlantic Forest. Almost 80% of the territory in the municipality of Lavras, in the south of the state, underwent anthropic change. In this work, we sought to understand the panorama of the conservation and recovery of natural ecosystems in the municipality of Lavras, fully inserted in the Atlantic Forest biome, by analyzing the databases and other literature that address the subject and conducting semi-structured interviews with representatives of the main groups that decide and impact this theme on a local scale. The low level of preservation of natural environments in the study area follows the scenario found in the municipalities of the Vertentes do Rio Grande hydrographic sub-basin. The interviewees presented a panorama in which there are few alternatives of public or private initiative for the recovery of municipal environments with already consolidated degradation, using the most effective compensation measures for new requests for intervention. Decree nº 48,127 of 2021 gains importance, having regulated the Environmental Regularization Program (PRA in Portuguese) in Minas Gerais, provided for in Federal Law nº 12,651 of 2012. The expectation is that the PRA can assist in the recovery of areas that have degraded throughout the state before 2008. Of the suggestions for improvements to this scenario, the one that had the greatest strength was implementing well-structured environmental education programs with a practical impact on rural landowners in the municipality.